After Interaction - Taylor, Alex (Interactions, 2015)
Alex S Taylor (2015) , Interactions 22(5), p. 48-53. It is, arguably, where it all began for interaction. Doug Engelbart's retrospectively titled "The Mother of All Demos" spectacularly set the scene for what we do in HCI and especially for what we imagine interaction to be. Engelbart and his team showcased a remarkable collection of technologies for seeing and manipulating data. The demo is best known for the introduction of the mouse as an input device, but also presented was an integrated teleconferencing system and the simultaneous collaborative editing of a text document. Think computing in the late 1960s, but with the mouse and something akin to Skype and Google Docs. It's hard to imagine how extraordinary this must have seemed at a time when telephone adoption was only just reaching a plateau in the U.S. and, for all but the technological elite, the idea of networked computers was the stuff of science fiction or, more likely, just unthought of.